Feasibility analysis of standalone photovoltaic electrification system in a residential building in Cyprus - Kamali, Saeed (Pergamon-Elsevier Science Ltd, 2016)
This research focuses on the design phases and economic analysis of a standalone photovoltaic system to electrify a house in the rural fringe of Famagusta, Cyprus. The designed system has the capability to cover residents' electricity demand (17.23 (kW h/day)) during the winter (with the lowest solar irradiation). Utilizing mathematical model, the PV panels area, PV peak power, the battery capacity, inverter and charge controller sizes were determined to be 46.73 (m(2)), 7.5 (kW), 44.78 (kW h), 2 (kW) and 350 (A) respectively. Moreover, the life cycle cost analysis was investigated. The life cycle cost of the system was found to be (TRY] 54,560 whereas the annualized life cycle cost and unit price of electricity was calculated to be around [TRY] 2700 and [TRY] 0.43 for each kilowatt-hour. It was concluded that a standalone photovoltaic system is economically and technically feasible and a viable technology for the electrification of a house in Cyprus. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Residential building; Standalone photovoltaic (PV) system; Sustainable energy; Zero-energy building; Life cycle cost analysis; Cyprus